# Solve for v (v-3)^2-27=0 (v-3)2-27=0
Add 27 to both sides of the equation.
(v-3)2=27
Take the square root of each side of the equation to set up the solution for v
(v-3)2⋅12=±27
Remove the perfect root factor v-3 under the radical to solve for v.
v-3=±27
Simplify the right side of the equation.
Rewrite 27 as 32⋅3.
Factor 9 out of 27.
v-3=±9(3)
Rewrite 9 as 32.
v-3=±32⋅3
v-3=±32⋅3
Pull terms out from under the radical.
v-3=±33
v-3=±33
The complete solution is the result of both the positive and negative portions of the solution.
First, use the positive value of the ± to find the first solution.
v-3=33
Add 3 to both sides of the equation.
v=33+3
Next, use the negative value of the ± to find the second solution.
v-3=-33
Add 3 to both sides of the equation.
v=-33+3
The complete solution is the result of both the positive and negative portions of the solution.
v=33+3,-33+3
v=33+3,-33+3
The result can be shown in multiple forms.
Exact Form:
v=33+3,-33+3
Decimal Form:
v=8.19615242…,-2.19615242…
Solve for v (v-3)^2-27=0

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top